Iron ore modified with alkaline earth metals for the chemical looping combustion of municipal solid waste derived syngas - Wang, Haiming (2022)
The redox performances of iron ore (IO) modified with different alkaline earth metals (AEM) as oxygen carriers (OCs) were evaluated with thermogravimetric analysis (TGA) and fluidized bed reactor experiments for the chemical looping combustion (CLC) of municipal solid waste (MSW) derived syngas. AEM oxides (BaO, CaO, and MgO) and AEM aluminates (BaAl2O4, CaAl2O4, and MgAl2O4) were systematically studied for their ability to promote the redox cycles performance of IO. Acid digestion, FESEM, and XRD analyses were conducted for the characterization of the OCs before and after redox reactions to investigate the promoting mechanism. It was found that the BaO-modified IO demonstrated the best reactivity with the reduction rate of 2.04%/min, which was twofold that of the pristine IO. AEM oxides presented superior redox performance than AEM aluminates owing to their strong interaction with Fe2O3 with the formation of AEM ferrites. The formed CaFe2O4 and MgFe2O4 with spinel structure and BaFe12O19 with hexagonal structure, as a result of the interaction, facilitated the lattice oxygen mobility and improved the reactivity of the modified IO. This interaction also increased the sintering resistance, while the morphology of the IO became more porous after redox cycles, which was also responsible for the improved performance during the long term CLC operation.